(3GdEYdGe HEQK Phi GdCQMGes - (3CMeO Hf YHO GdaJGM Gdedhis; (3GdeLjQj , TgGH GdOjf CHh GdYHGS CMeO Hf YHO GdaJGM Hf jhSa Hf YeQ Gdedhj GdTGaYj,J (B1181 (3g` s ((3eMeO GdSjhSi s)
(3ChdgG (B:s
(3hHYO, agPG TQM Ydi fXe cjajI JhQjK Phi GdCQMGe ddTjN GdYGQa HGddg s
(3BNQgG (B:s
(3hddYeI GdTbjbI SJI hKdGKhf hdcd Yeg ef GdHGbjf EKfi YTQ hGddg CYde HGdUhGH s
(3HgG fXGe GdJYbjHIs
(3ZjQ eagQSs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B152 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B278s
Keywords: (3Yde GdaQGFVs